2009
DOI: 10.1097/hjh.0b013e328317a74d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Gly460Trp α-adducin gene variant and diuretics on the risk of myocardial infarction

Abstract: This study suggests that the alpha-adducin gene does not play an important role in modifying the risk of nonfatal MI associated with the use of thiazide diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Further, a recent analysis in the Rotterdam study demonstrated an association of the Gly460Trp allele with higher risk of stroke (HR = 1.22; 95% CI, 1.02 to 1.45) and myocardial infarction (HR=1.33; 95% CI, 1.05 to 1.69). However, a recent study did not find an interaction effect of the Gly460Trp variant with thiazide diuretics treatment in either the wild-type or the minor allele carriers [45].…”
Section: Future Studies and Pharmacogenomicsmentioning
confidence: 98%
“…Further, a recent analysis in the Rotterdam study demonstrated an association of the Gly460Trp allele with higher risk of stroke (HR = 1.22; 95% CI, 1.02 to 1.45) and myocardial infarction (HR=1.33; 95% CI, 1.05 to 1.69). However, a recent study did not find an interaction effect of the Gly460Trp variant with thiazide diuretics treatment in either the wild-type or the minor allele carriers [45].…”
Section: Future Studies and Pharmacogenomicsmentioning
confidence: 98%
“…Ptsay et al demonstrated that the minor allele carriers of the ADD1gene taking thiazide diuretic therapy were at lower risk of suffering from myocardial infarction or stroke compared to wild-type patients, suggesting that in the presence of constitutive enhanced tubular sodium reabsorption, drugs such as diuretics should trigger less counter-regulatory mechanisms, thus yielding a more beneficial therapeutic effect [203]. However, again these findings were not replicated in larger controlled clinical trials [204][205][206]. Interestingly, ADD1 Gly460Trp, WNK1, and NEDD4L (rs4149601) specific haplotypes were found to significantly interact to control systolic blood pressure after thiazide diuretic therapy, suggesting the need to investigate the gene-gene interactions to detect significant pharmacogenetics effects [178,207].…”
Section: Pharmacogenetics and Pharmacogenomics Of Antihypertensive Drugsmentioning
confidence: 89%
“…Parallel studies in a hypertensive rat model and in human patients have indicated that the Gly460Trp polymorphism is associated with alterations in ADD1 function that may affect constitutive tubular sodium reabsorption [141,142]. While initially diuretic therapy in carriers of the ADD1 460Trp variant was associated with a positive response to treatment, several recent studies have failed to replicate this finding [56,117,143,144]. This controversy has been proposed to be attributable to differences in environmental factors, ethnic background and lifestyle of patients across different studies [135,144].…”
Section: Add1 Polymorphisms and Diuretic Drug Responsementioning
confidence: 94%
“…While initially diuretic therapy in carriers of the ADD1 460Trp variant was associated with a positive response to treatment, several recent studies have failed to replicate this finding [56,117,143,144]. This controversy has been proposed to be attributable to differences in environmental factors, ethnic background and lifestyle of patients across different studies [135,144]. Of all genes assessed to date, ADD1 is the most relevant in response to diuretic treatment however, additional players may surface through future large scale pharmacogenetic studies.…”
Section: Add1 Polymorphisms and Diuretic Drug Responsementioning
confidence: 94%